Children born weighing less than 1701 g: visual and cognitive outcomes at 11–14 years. Issue 4 (16th February 2007) - Stephenson, Terence; Wright, Sharon; O'Connor, Anna; Fielder, Alistair; Johnson, Ann; Ratib, Sonia; Tobin, Michael
Abstract : Background and objective: Few studies of low birthweight children have explored the relationship between later visual morbidity and neuropsychological function. This study evaluated these outcomes using a geographically defined cohort. Methods: Prospective study of retinopathy of prematurity (ROP) in infants born weighing <1701 g, undertaken in 1985–7. 254 of the survivors consented to ophthalmic examination at 10–13 years. Four children were severely disabled and could not complete the tests. 198 of the remaining agreed to neuropsychological assessment at 11–14 years (British Ability Scales II (BAS), Movement Assessment Battery (ABC), Neale Analysis of Reading Ability). Results: At 10–13 years, 99/198 children had an adverse ophthalmic outcome (AOO) (reduced acuity n = 48, myopia n = 40, strabismus n = 36, colour defect n = 2, field defect n = 1). There were no significant differences between children with AOO and those with a normal ophthalmic outcome with regard to sex, gestation, birth weight, neonatal cranial scan appearances and social class. 106/198 had ROP; 98 had mild ROP with no increased risk of AOO in later childhood. All eight children with severe ROP had an AOO in later childhood. Children with an AOO performed worse on the BAS, ABC and reading ability tests. Conclusions: At age 10–13, 50% of children born <1701 g have an AOO. These children are not simply those with earlier gestations, lower birth weight or ROP. Children with AOO have a worse neuropsychological outcome. The next step is to determine whether there are visual interventions which can improve ophthalmic outcome and whether a better neuropsychological outcome follows.